Reconstruction of Maqashid Shari'ah Perspective Muhammad Thahir Ibn 'Assyria: Efforts to Re-Discuss Sharia with Reality - Muhammad Aziz; Sholikah; Abdul Hadi; Abdul Ghofur (Jurnal Hukum Islam, 2019)
The spirit and essence of everything that is prescribed by Islam, is basically between bringing benefit to humans and preventing danger to humans. So, it is important to know other than undergoing all the shari'a that Allah entrusts to his servant, namely to know and determine the ins and outs of the intent and purpose of the preservation of a certain law. In this study, put a big response to the hard efforts of Ibn 'Asyur in reformulating universal legal concepts which were then called the science of maqashid al-sharia. This is important, because approaching the universality of the Shari'a is one of the vital elves that is needed, especially in the era of globalization like today which presupposes a fast-paced change and was not taken into account before. According to Ibn 'Asyur, the main reason for the decline of fiqh is that the scholars are ignorant of the study of maqashid, and this will lead us to castrate the values of the Shari'a itself. In line with Ibn 'Asyur, Alal al-Fasi, one of the experts in contemporary maqashid al-sharia also views that the main condition for success in dialoguing fiqh with contemporary reality today is the massive response of scholars on the study of maqashid. This is where the function and role of maqashid al-shari'ah find its momentum. Its elastic character, across space and time is expected to be able to dialectically with problems that continue to emerge.